12-2r-4r=r-6-4r

Simple and best practice solution for 12-2r-4r=r-6-4r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-2r-4r=r-6-4r equation:


Simplifying
12 + -2r + -4r = r + -6 + -4r

Combine like terms: -2r + -4r = -6r
12 + -6r = r + -6 + -4r

Reorder the terms:
12 + -6r = -6 + r + -4r

Combine like terms: r + -4r = -3r
12 + -6r = -6 + -3r

Solving
12 + -6r = -6 + -3r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '3r' to each side of the equation.
12 + -6r + 3r = -6 + -3r + 3r

Combine like terms: -6r + 3r = -3r
12 + -3r = -6 + -3r + 3r

Combine like terms: -3r + 3r = 0
12 + -3r = -6 + 0
12 + -3r = -6

Add '-12' to each side of the equation.
12 + -12 + -3r = -6 + -12

Combine like terms: 12 + -12 = 0
0 + -3r = -6 + -12
-3r = -6 + -12

Combine like terms: -6 + -12 = -18
-3r = -18

Divide each side by '-3'.
r = 6

Simplifying
r = 6

See similar equations:

| (2y-3)(7y-1)= | | 7(w-3)=-21 | | 115000=0.5x^2+15x+5000 | | -8(-8k-6)=-6k-22 | | 2+1.25x= | | x^2-18x+12=0 | | 0=(x^2)-56x+104 | | 1/x+1+2/x-1=5/4 | | 14000=0.125x^2+20x+5000 | | x^3=500000000 | | -7x=-5-12 | | 0.40x+0.05(18-x)=0.10(-26) | | 6(2m+3)=5(4m+2) | | -3.2=w+(-0.2) | | 4x+66=90 | | 20=16-y/5 | | -0.10(17)+0.40x=0.05(x-6) | | 3x+18=10x-59 | | 46+3y-19=12y-9-3y | | 0.11y+0.03(y+6000)=740 | | 1.2-(-0.5)=d | | p+16=2p-4+3p | | 9x+x=3x+44 | | X+2x+3x=46 | | 5t+1/2=t+5/4+t-3/4 | | 6(7-g)=12 | | 6(7-9)=12 | | y=1.2x+4 | | x-5/3+5/3=-x/5 | | -3r(4r-8)=-36 | | 40-8x=80-10x | | 2(r+1)=18+4r |

Equations solver categories